PERALIHAN MATA PENCAHARIAN PEKERJA HOTEL YANG TERDAMPAK KRISIS EKONOMI (PANDEMI COVID-19) - Salsabila, Vina Adhi; Maryunani, Maryunani (Journal of Development Economic and Social Studies, 2022)
The travel ban policy during the Covid-19 pandemic  in 2020  has reduced the income of tourism sector in Batu city, marked by the decrease in number of  visitors and  room occupancy rate. This condition  has slowed tourism sector down and made most of the businesses laid off their employees.  In 2011, 116 employees in tourism sector were dismissed from their  job due to economic crisis caused by the Covid-19 pandemic. To fulfill their daily needs, they have to find other jobs. The objective of this research is  to identify and analyze the shifting of jobs in tourism sector affected by the pandemic and its consequences. The data of this descriptive research was harvested from interviews with and observations on 69 released hotel employees. This study finds that the shifting did occur, but shifting to other sectors did not happen. The shifting did occur in the service sector but only to other fields, such as tourism outsourcing and engineering, entrepreneurship, agriculture, animal husbandry, etc. The consequence of the job shifting  is the decrease of income, which leads to lower purchasing power. In order to increase the purchasing power, the government should provide direct cash assistance (BLT) so that affected people can still make consumption. This measure can help Batu city maintain their economy through consumptive instrument.